THE STRATEGIC ORIENTATION OF THE PUBLIC DEBT MANAGEMENT AT THE TIME OF UNCERTAINTY - D. Ayad Taher Mohammed AL-Jubouri; Alaa Gameel Abdul Reda (Scholar Express Journal, 2022)
During the last decade of the twentieth century, public debt management strategies dealt with a limited number of challenges such as the volatility of exchange rates and interest rates. Yet, the liberalization of financial markets, opportunities and challenges arising from the globalization of public debt markets and international financial crises, highlighted the weaknesses in the debt management strategies if there is no organized approach to risks. The strategic goals were badly identified with a complete lack of understanding or debt -related data. In addition, there was a clear confusion in the relevant institutional arrangements of dealing with debt and implement the strategy. The current research uses the descriptive analytical approach to review the concept of debt management strategies and its formulation and implementation requirements based on the understanding of the nature of the relationship between the macroeconomic economy and the strategy of sovereign debt
Keywords: Public debt; management; government; sovereign